Information literacy instruction : - Grassian, Esther S. (Neal-Schuman, 2009)
In-depth discussion of both the theory and practice of library instruction. Chapters cover the history and background of user education in libraries; the psychology of learning as applied to library teaching; conceptual models for teaching critical thinking; program management, planning, and politics (on and off-campus); assessment and evaluation; designing and developing print and electronic teaching materials; classroom management and teaching techniques; learning technology; visions for the future and much more. The CD includes tables describing various instructional modes, an interactive database to aid in selecting among them, handouts for in-house training or personal use, and more.